2020
DOI: 10.1186/s12935-020-01172-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of nicastrin on hepatocellular carcinoma proliferation and apoptosis through PI3K/AKT signalling pathway modulation

Abstract: Background: Increasing evidence has proven that the γ-secretase complex plays significant roles in the carcinogenesis of malignancies. However, the independent effect of nicastrin (NCSTN), the largest constituent of the γ-secretase complex, on the progression of hepatocellular carcinoma (HCC) remains to be discovered. Methods:In our study, we used open online databases, including the Oncomine database, GEPIA and KMPlotter, to analyse the expression of 4 genes and their correlation with prognosis in HCC. NCSTN … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…For AKT signalling (Fig. 5 ), we found the decreased expressions of NCSTN [ 43 ], TPD52L2 [ 44 ], PSMC2 [ 45 ], FKBP4 [ 46 ] and ARHGAP1 [ 47 ] which activate AKT signalling (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…For AKT signalling (Fig. 5 ), we found the decreased expressions of NCSTN [ 43 ], TPD52L2 [ 44 ], PSMC2 [ 45 ], FKBP4 [ 46 ] and ARHGAP1 [ 47 ] which activate AKT signalling (Fig. 4 ).…”
Section: Resultsmentioning
confidence: 99%
“…AKT is a clinically common serine/threonine‐specific protein kinase, and its phosphorylated form is p‐AKT, which shows biological activity. With homology to protein kinases A and C, AKT is also known as protein kinase B (PKB) (Ma et al., 2020; Wang et al., 2020). p‐Akt is a cell cycle regulator, proliferation promoter, and apoptosis inhibitor by acting on its downstream molecules.…”
Section: Discussionmentioning
confidence: 99%
“…MK-2206 inhibits the autophosphorylation of AKT at threonine 308 and serine 473 (21). Preclinical studies have shown that MK-2206 has an inhibitory effect on human cancer cell lines, such as breast, lung, colon and liver cancer (22)(23)(24)(25). PI3K/AKT/HIF-1α reportedly induces chemoresistance in liver cancer cells (26,27), and LY-294002 can enhance the chemosensitivity of liver cancer (28).…”
Section: Ly-294002 Enhances the Chemosensitivity Of Liver Cancer To Oxaliplatin By Blocking The Pi3k/akt/hif-1α Pathwaymentioning
confidence: 99%